1997
DOI: 10.1002/jlb.62.5.604
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of the CXC chemokine ENA-78 in monocytes and its role in disease

Abstract: Epithelial neutrophil-activating protein 78 (ENA-78) is a member of the CXC chemokines and acts as a potent chemoattractant and activator of neutrophil function. On stimulation in vitro, ENA-78 is highly expressed in many cell types. ENA-78 protein levels are strongly elevated in synovial fluid and blood of patients with rheumatoid arthritis. By in situ hybridization and immunofluorescence staining, ENA-78 has been recognized as a major CXC chemokine expressed in epithelial cells of the intestinal mucosa of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
103
0
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(112 citation statements)
references
References 0 publications
3
103
0
6
Order By: Relevance
“…GITR is expressed by T regulatory cells (Treg) as well as activated T cells and NK cells. ENA-78 produced by monocytes, macrophages, fibroblasts, endothelial cells, and several types of epithelial cells is a member of the CXC family of chemokines, and acts as a potent chemoattractant and activator of neutrophil function as well as an angiogenic factor in cancer [20,21] In the cytokine antibody array portion of our study, HGF in prostatic fluid was the cytokine most increased in extensive disease cases, a finding that was confirmed statistically by ELISA. HGF, which can be derived from a variety of tissues, is known to be elevated in the serum of men with metastatic prostate cancer [22].…”
Section: Discussionsupporting
confidence: 63%
“…GITR is expressed by T regulatory cells (Treg) as well as activated T cells and NK cells. ENA-78 produced by monocytes, macrophages, fibroblasts, endothelial cells, and several types of epithelial cells is a member of the CXC family of chemokines, and acts as a potent chemoattractant and activator of neutrophil function as well as an angiogenic factor in cancer [20,21] In the cytokine antibody array portion of our study, HGF in prostatic fluid was the cytokine most increased in extensive disease cases, a finding that was confirmed statistically by ELISA. HGF, which can be derived from a variety of tissues, is known to be elevated in the serum of men with metastatic prostate cancer [22].…”
Section: Discussionsupporting
confidence: 63%
“…The lack of relation may be explained by the fact that these molecules are secreted into the circulation by various cells in different tissues. 35,36 Regarding the plasma levels of TNF-a, we did not find any changes in response to the weight reduction protocol. Similar conclusions were reached in several clinical studies with different lengths and types of diets recently reviewed by Klimcakova et al 37 Moreover, Mohamed-Ali et al 38 showed that AT is a poor contributor to circulating levels of TNF-a.…”
Section: Discussionmentioning
confidence: 61%
“…Thus, more aspects on the interaction between HSCs and immune cells remain to be determined. For example, ENA-78 acts as a potent chemoattractant and activator of neutrophil function, 35 and eotaxin is a potent eosinophil chemoattractant. 36 Other cytokines and chemokines up-regulated at senescence are expressed and secreted by HSCs, such as IL-6 37 and IL-8.…”
Section: Discussionmentioning
confidence: 99%